GYROSCOPE AND ITS APPLICATIONS - Pazilova Shokxida Abdulbasitovna (Bright Mind Publishing, 2025)
This article discusses the history of gyroscopes, their main properties, types, and applications in various fields of technology and weapons. It also highlights the main components of a gyroscope and its drawbacks.
Keywords: Direction, rotation, gyroscope, stabilization, navigation, control, device, gyroscopic effect.